2022
DOI: 10.1186/s13256-021-03244-z
|View full text |Cite
|
Sign up to set email alerts
|

Complete heart block ensuing from a metastatic small cell carcinoma: a case report

Abstract: Introduction Notwithstanding the diagnostic and therapeutic advancements, the incidence of cardiac metastases has increased in recent decades. Lung cancers are the most common primary malignant neoplasms with cardiac metastasis potential. The clinical presentation of cardiac metastases is either silent or vague, and largely depends on the infiltrated location and tumor burden. Although arrhythmias are not uncommon in metastatic cardiac tumors, complete heart block is relatively a rare manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…After an extensive search, we discovered that none of the 7 precedents reported cases involving cardiac invasion of SCLC had surgical resection of the lung cancer ( Table 1 ) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Most patients were not eligible for surgery because of poor health or the presence of multiple extrapulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%
“…After an extensive search, we discovered that none of the 7 precedents reported cases involving cardiac invasion of SCLC had surgical resection of the lung cancer ( Table 1 ) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Most patients were not eligible for surgery because of poor health or the presence of multiple extrapulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although echocardiography is excellent in the diagnosis of MCT, small field of view and insufficient acoustic window limit its application. Sometimes echocardiographic findings is normal in patients with cardiac metastases 14 . While CMR is the gold standard for the definition of the nature of intracardiac masses and their relationship to paracardiac structures 15 .…”
Section: Discussionmentioning
confidence: 99%
“…CMR allows optimal tumor characterization with superior depiction of soft tissues and provides accurate evaluation of cardiac structure and function to complement echocardiography and provide early detection and management 16,17 . The benefits of CMR over echocardiography in studying cardiac tumors has been recognized 14 . Previous study suggested that cardiac metastases can be mistaken for thrombi, endocarditis, or primary tumors in echocardiograms, supplemental imaging with CMR is often needed for further characterization 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations